2014
DOI: 10.1371/journal.pntd.0003268
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a Plasmodium vivax Circumsporozoite Protein-Based Vaccine in Aotus nancymaae Is Associated with Antibodies to the Repeat Region

Abstract: We have previously reported that Vivax Malaria Protein 001 (VMP001), a vaccine candidate based on the circumsporozoite protein of Plasmodium vivax, is immunogenic in mice and rhesus monkeys in the presence of various adjuvants. In the present study, we evaluated the immunogenicity and efficacy of VMP001 formulated with a TLR9 agonist in a water-in-oil emulsion. Following immunization, the vaccine efficacy was assessed by challenging Aotus nancymaae monkeys with P. vivax sporozoites. Monkeys from both the low- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 22 publications
(28 reference statements)
1
36
0
Order By: Relevance
“…Sixty six percent of vaccinated monkeys were completely protected following challenge with P. vivax sporozoites. Antibodies against the repeat region of PvCSP showed a statistical association with protection [38]. VMP001 has also been formulated in nanoparticles formed as interbilayer crosslinked multilamellar lipid vesicles (ICMVs) composed of polylactide-co-glycolide acid (PLGA) and a lipid membrane [39,40].…”
Section: Leading P Vivax Vaccine Candidatesmentioning
confidence: 99%
“…Sixty six percent of vaccinated monkeys were completely protected following challenge with P. vivax sporozoites. Antibodies against the repeat region of PvCSP showed a statistical association with protection [38]. VMP001 has also been formulated in nanoparticles formed as interbilayer crosslinked multilamellar lipid vesicles (ICMVs) composed of polylactide-co-glycolide acid (PLGA) and a lipid membrane [39,40].…”
Section: Leading P Vivax Vaccine Candidatesmentioning
confidence: 99%
“…The superior immunogenicity of particulate or arrayed malaria antigens in the context of VLPs (in comparison to soluble antigen) is consistent across a number of subunit vaccine development efforts for different life cycle stages. Indeed, a more recent comparison of VLPs versus soluble antigen for P. vivax CSP showed similar results in NHPs (Vanloubbeeck et al, 2013), with promising efficacy reported in Aotus monkeys (Yadava et al, 2014).…”
Section: Rtssmentioning
confidence: 77%
“…Unlike the P . falciparum vaccine, it underwent additional extensive testing and was advanced into humans following two separate, preclinical immunogenicity [10] and efficacy [11] studies conducted in nonhuman primates.…”
Section: Recombinant P Vivax Csp Vaccinementioning
confidence: 99%